Evaluation of the PBJT Tax Rate Adjustment for Arts and Entertainment Services in the Province of DKI Jakarta - Saragi, Dea Grace; Abbas, Yulianti (E-Jurnal Akuntansi, 2026)
The policy of adjusting the PBJT tariff for Arts and Entertainment Services is intended to strengthen regional tax revenue and enhance regional fiscal autonomy. However, the implementation of a significant tariff increase poses a threat to the sustainability of businesses in the entertainment industry sector. This study aims to evaluate the policy on changes to the PBJT tariff for Arts and Entertainment Services implemented by the Provincial Government of DKI Jakarta based on Dunn’s (2003) policy evaluation theory. The findings indicate that, overall, the adjustment of the PBJT tariff for Arts and Entertainment Services in DKI Jakarta has been less effective in optimizing PBJT revenue from the arts and entertainment sector. Several obstacles to revenue optimization remain and require improvement, including coordination among stakeholders, human resource capacity, and the equitable provision of fiscal incentives for PBJT taxpayers in the arts and entertainment sector.